Pengaruh Intensitas Kebisingan Terhadap Peningkatan Denyut Nadi Di Bagian Process Dan Finishing PT. Iskandar Indah Printing Textile Surakarta - Murni, Murni (2012)
Noise is unwanted noise from the business or activities within a particular level time and that can affect human health and environmental comfort. Noise causes various disorders of labor, such as physiological disorders, psychological disorders, communication disorders and deafness, it also causes disruption to the hearing impaired such as communications, safety hazards, decreased work performance, fatigue and stress. The purpose of this study was to investigate the effect of noise intensity on work stress of workers at the winding and finishing site PT. Iskandar Indah textile Printing of Surakarta. This research used analytical observational method with cross sectional approach. The population in this study were employees at the winding and finshing site in PT. Iskandar Indah Textile Printing as many as 83 people. Statistical was done the Mann Whithney-Test. The results showed that the intensity of the noise in the winding exceeds a predetermined NAB ie 90, 33 dB (A) with the highest intensity value was 93 dB (A) and the lowest intensity value was 88 dB (A), while the intensity of the noise at the finishing site average was 80 dB (a) with the highest intensity was 82 dB (a) and the lowest intensity was 72 dB (a). Statistical test results obtained in this study was the influence of noise on the intensity of the risk of job stress on the winding and finishing PT. Iskandar Indah Textile Printing Surakarta p = 0.002.